Effect of intensity manipulation of Olympic lift training on the sprinting ability of 100 meters sprinters - Yadav, S.; Basumatary, B.; Dureha, D. K. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The purpose of the present study was to assess the effect of intensity manipulation of Olympic lift training on the sprinting ability of 100 meters sprinters. The subjects were 30 male elite sprinters of 18 to 25 years of age group from Lakshmibai National Institute of Physical Education, NERC. They were assigned into 2 groups: A (Intensity manipulation of Olympic lift training; n=15) and B (control; n=15). The training was given for a period of 6 weeks. The experimental groups were trained thrice a week, while the control group continued with their daily routine work. The performances of sprinting ability of the subjects were taken by the Smart Block. The different sprinting ability- Run time, Raw time, Reaction time, Peak force (R), Peak force (L) Push time and Timed runs were measured with the use of a smart block The between-group differences were assessed using the student`s t-test for dependent data. The level of p 0.05 was considered significant. Significant between-group differences were found for Run time (t=3.00*), Raw time (t=3.03*), Reaction time (t=5.84*), Peak force (R) (t=4.40*), Peak force (L) (t=3.82*), Push time (t=2.48*), and Timed runs (t=2.93*), since the computed value of t for all the dimensions were greater than the tabulated t.05 (14) =2.145. The result was found that the sprinters significant difference in their sprinting ability components